Definicja terroryzmu międzynarodowego - Michalus, Jacek L. (Wydział Prawa i Administracji UAM, 1993)
The article's content is connected with the several-decade-old attempts to elaborate a definition of international terrorism to be commonly accepted by the international community. Statistical data concerning international terrorism are presented and the history of international law actions aiming at a convention on preventing and combatting international terrorism are described. The attention is, however, primarily focused on questions directly related to the definition of international terrorism. The scope of the phenomenon is discussed in detail both from the subject- related and the object-related viewpoints, and so are the elements constitutive of its international nature. The matter of the impact of the perpetrators' motives on the qualification of their acts is also considered.
The definition of international terrorism